Forcing: posets, boolean algebras and sheaves - Smykalla, Michel Viana (2024)
The forcing method was first introduced by Paul J. Cohen to prove the independence of the Continuum Hypothesis of George F. L. P. Cantor from the axioms of the Zermelo-Fränkel Set Theory. In this work, we present three forms of this technique: Forcing through partial orders, forcing using Boolean-valued models, and a sheaf-theoretic approach. Moreover, contributions towards how to relate these versions of forcing are part of this MSc thesis.